Formative assessment for teaching & learning - Boyle, Bill 4 0 (William F.),16; Charles, Marie; 5 (Los Angeles : SAGE, 2014)
This books shows how to develop your planning for learner-centred day-to-day teaching and learning situations through an understanding of formative teaching, learning and assessment--Publisher.
Includes bibliographical references (pages 209-224) and index.
Professional;Professional.
Keywords: 2 -- 0; 6; Educational tests and measurements.;Effective teaching.;Educational tests and measurements.;Effective teaching; 20; 2